The research, evaluation and guidance supervisors experiential backgrounds and functions - Ruiz, Lirio (Manuel) 1920- ([Quezon City s.n.], 1971)
This study presents the experiential backgrounds of the Research, Evaluation and Guidance supervisors and an analysis of their functions. Sources of data were annual reports of twenty-four supervisors of research, evaluation and guidance for the school year 1969-1970; the personal files of the 24 supervisors which are on file at the Records Section of the Bureau of Public Schools and the interview schedules conducted with the Research, Evaluation and Guidance Supervisors of two school divisions.
Thesis (M. Ed.)--University of the Philippines.
Keywords: Personnel service in education -- Philippines